2012
DOI: 10.1159/000335231
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Anaphylactic Reactions: An Uncommon Debut of Lymphocytic Hypophysitis

Abstract: We report on a 24-year-old male, with exercise-induced asthma and intermittent abdominal pain since puberty, who suffered from recurrent anaphylactic reactions. He also complained of occasional headaches. After extensive studies he was eventually diagnosed with idiopathic anaphylaxis, once the following diagnoses had been excluded: allergic origin [foods (including ω5-gliadin), latex and drugs], hydatidosis, carcinoid syndrome, systemic mastocytosis, autonomic epilepsy, hereditary angioedema, pheocromocitoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Several case reports have identified rare causes of anaphylaxis in patients who were initially diagnosed with IA. Such causes of anaphylaxis include pigeon tick, A. Reflexus ,25 lymphocytic hypophysitis in the context of complicated adrenal crises in an asthmatic patient,26 and wheat-dependent exercise-induced anaphylaxis 27. In fact, in a study done by Heaps et al, 2014,28 wheat protein, omega-5-gliadin, and shrimp were the main causes of anaphylaxis in the study’s cohort of patients who were initially diagnosed with IA.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Several case reports have identified rare causes of anaphylaxis in patients who were initially diagnosed with IA. Such causes of anaphylaxis include pigeon tick, A. Reflexus ,25 lymphocytic hypophysitis in the context of complicated adrenal crises in an asthmatic patient,26 and wheat-dependent exercise-induced anaphylaxis 27. In fact, in a study done by Heaps et al, 2014,28 wheat protein, omega-5-gliadin, and shrimp were the main causes of anaphylaxis in the study’s cohort of patients who were initially diagnosed with IA.…”
Section: Resultsmentioning
confidence: 87%
“…Doses of omalizumab ranged from 225 to 375 mg administered at a frequency of every two, four, or eight weeks. The majority of these studies reported resolution of IA episodes that was maintained over 12 months after stopping omalizumab treatment 1214,21,26,3538. Two case reports included in this review have described relapse in two patients after a short period of treatment (three and four months of treatment) and an adverse event (anaphylaxis) in another patient undergoing omalizumab treatment for frequent IA episodes 15,39…”
Section: Resultsmentioning
confidence: 99%
“…Low GC levels due to adrenal insufficiency may have led to the dysregulation of these parameters, promoting an overshoot of the allergic reaction and making the patient more susceptible to anaphylaxis. For example, adrenal insufficiency triggered by lymphocytic hypophysitis was reported to induce repeated anaphylaxis [ 11 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%